The Research Analisis terhadap Manajemen Program Organisasi Pemuda Persatuan Islam Cabang Margaasih - Fatchur Rizka Zubaidi; Enoh; Alhamuddin (UNISBA Press, 2022)
Abstract. Indonesian society that is experiencing a multidimensional crisis requires positive and innovative changes (Basit, 2009: 2) For this reason, youth need to get a place and attention from various elements of society. In overcoming social problems in society, especially with regard to youth development problems, it is not only the responsibility of individuals, but social problems are the responsibility of all components of society. PERSIS youth organization is one of the non-formal educational institutions in the community that has an important role in providing guidance to the surrounding youth. PERSIS is an alternative as a forum for youth to carry out various positive activities such as being creative, developing talent through the organization as well, they get an Islamic environment and can develop creativity and can convey moral messages to the community and youth through religious activities or social activities carried out in the community. community environment. PERSIS organization one of the goals of this organization is to strengthen the identity of PERSIS youth as the successor of the da'wah struggle to form a superior Muslim personality, provide a forum to accommodate aspirations and foster intellectuality for the development of Islamic thought and foster ukhuwah Islamiyah. To achieve this goal the PERSIS youth organization has successfully held various youth development programs such as: Da'wah, Education, Social, Economics, Sports and the Arts. Abstrak. Masyarakat Indonesia yang sedang mengalami krisis multidimensional membutuhkan adanya perubahan-perubahan yang positif dan inovatif (Basit, 2009:2) Untuk itulah, pemuda perlu mendapatkan tempat dan perhatian dari berbagai elemen masyarakat. dalam mengatasi permasalahan sosial di masyarakat terlebih berkenaan dengan permasalahan pembinaan pemuda tidak hanya menjadi tanggungjawab perorangan saja, tetapi permasalahan sosial menjadi tangungjawab seluruh komponen masyarakat. Organisasi pemuda PERSIS merupakan salah satu lembaga pendidikan non formal di masyarakat yang memiliki peran penting dalam memberikan pembinaan kepada pemuda disekitarnya. PERSIS merupakan salah satu alternatif sebagai wadah pemuda untuk melakukan berbagai aktivitas positif seperti berkreasi, mengembangkan bakat melalui organisasi tersebut juga, mereka memperoleh lingkungan yang Islami serta dapat mengembangkan kreativitas dan bisa menyampaikan pesan moral kepada masyarakat dan pemuda melalui kegiatan keagamaan ataupun kegiatan sosial yang dilakukan di lingkungan masyarakat. organisasi PERSIS salah satu tujuan organisasi ini adalah mengokohkan identitas pemuda PERSIS sebagai penerus perjuangan dakwah membentuk pribadi muslim yang unggul, menyediakan wadah untuk menampung aspirasi dan membina intelektualitas bagi perkembangan pemikiran Islam dan membina ukhuwah Islamiyah. Untuk mencapai tujuan tersebut organisasi pemuda PERSIS telah berhasil mengadakan berbagai program pembinaan pemuda seperti : Dakwah, Pendidikan, Sosial, Ekonomi, Olahraga dan Kesenian.